A splicing site change between exon 5 and 6 of the nuclear-encoded chloroplast-localized HvYGL8 gene results in reduced chlorophyll content and plant height in barley - Xia, Xue; Liu, Lei; Cai, Kangfeng; Song, Xiujuan; Yue, Wenhao; Wang, Junmei (Frontiers in Plant Science, 2023)
The chloroplast is an important cellular organelle and metabolic hub, which is not only responsible for plant photosynthesis but also involved in de novo biosynthesis of pigments, fatty acids and hormone metabolisms. Plenty of genes responsible for rice leaf color variations have been reported involved in chlorophyll biosynthesis and chloroplast development directly or indirectly, whereas few genes were functionally confirmed for leaf color changes in barley at the molecular level. In this study, we obtained a yellow leaf and dwarf ygl8 mutant from the progeny of barley variety Morex seeds treated by EMS. We performed the Bulked-Segregant Analysis (BSA) and RNA-Seq analysis, and targeted an UMP kinase encoding gene YGL8, which generated a splicing site change between exon 5 and 6 of YGL8 due to G to A singlenucleotide transition in the 5 th exon/intron junction in ygl8 mutant. The splicing site change between exon 5 and 6 of YGL8 had no effects on the chloroplast subcellular localization, but resulted in an additional loop in the UMP kinase domain, which might disturb the access of the substrates. On one hand, the splicing site change between exon 5 and 6 of YGL8 down regulated the transcriptional expressions of chloroplast-encoded genes and chlorophyll biosynthesis related genes in a temperature-dependent manner in ygl8 mutant. On the other hand, the down regulations of bioactive GA biosynthesis related GA20ox genes and cell wall cellulose biosynthesis related CesA genes were also observed in ygl8 mutant, which led to the reduced Deleted: Alternative splicing